Effect of restricted feeding on productivity of Mojosari x Alabio cross-bred layer ducks (MA): 2. Second phase of laying from 44-67 weeks old - Ketaren, P.P; Prasetyo, L.H (Indonesian Animal Sciences Society, 2002)
Productivity and feed efficiency of Mojosari Alabio (MA) cross-bred duck on the first phase of laying from 20-43 weeks old was better when fed ad lib. using pelleted diet. An experiment was conducted to evaluate effect of restricted feeding of pelleted diet on second phase of laying of MA cross-bred duck performances from 44-67 weeks old. The experiment was designed in a Completely Randomized Design. 156 MA cross-bred ducks were devided into three groups and fed three experimental diets: (1) 70% ad lib., (2) 85% ad lib. and (3) ad lib. All experimental diets were fed to ducks for 24 weeks and feed intake, egg production, egg weight, FCR, molting, egg yolk weight, albumen weight, egg shell weight and egg yolk colour score were measured as parameters. The results showed that the restricted feeding of 70 and 85% significantly (P<0.05) reduced egg production, egg weight and egg yolk percentage, egg yolk colour score and induced early molting, but did not adversely affect egg white and egg shell percentage. FCR of duck fed 70% (6.47) was significantly (P<0.05) the worst compared to the duck fed 85% (4.13) and ad lib. (3.55). The results indicate that MA cross-bred duck was more efficient being fed ad lib. Key words: Restricted feeding, MA crossbred duck, productivity and egg quality